Reducing chronic medical complications due to failure of patient safety using Standardized Plant Analysis Risk-Human Reliability Analysis (SPAR-H) method - Modabber, Mohammad Reza; Ahmadi, Batoul; Mosadeghrad, Ali Mohammad (Chronic Diseases Journal, 2019)
BACKGROUND: Human errors in the medical profession can lead to irreparable errors in people's lives, damage, and heavy costs. Among health care workers, nurses spend more time with patients compared to other personnel; hence, they are more prone to human error. Therefore, the purpose of this study was to identify and evaluate human errors using the Standardized Plant Analysis Risk-Human Reliability Analysis (SPAR-H) method in nursing staff of a general hospital in Qazvin Province, Iran. METHODS: This cross-sectional study was conducted in a general hospital in Qazvin during last 6 months of 2016 and first 6 months of 2017. The target population in the present study was nursing groups based on their highest work experience, from each section in hospital. The SPAR-H method was used to investigate human error in the population and the collected data were analyzed using SPSS software. RESULTS: The highest error related to inappropriate venipuncture with probability of 0.7, and the least probable error related to error in entering the numbers of vital signs with the probability of 0.0045. CONCLUSION: Due to the sensitivity of the role of nurses in hospitals, the need for increased workforce, the use of people with higher work experience in sensitive sectors, reducing overtime even for those who volunteered to work overtime, scientific scheduling of the personnel’s work shifts, and providing practical training such as stress control methods in case of emergencies can be effective in reducing the probability of an error.